A genome-wide association study of biomass yield and feed quality in buffel grass (Cenchrus ciliaris L.) - Negawo, Alemayehu T.; Muktar, Meki S.; Gutiérrez, R.A.S.; Habte, Ermias; Muchugi, Alice; Jones, Christopher S. (MDPI, 2024)
The development of modern genomic tools has helped accelerate genetic gains in the breeding program of food crops. More recently, genomic resources have been developed for tropical forages, providing key resources for developing new climate-resilient high-yielding forage varieties. In this study, we present a genome-wide association study for biomass yield and feed quality traits in buffel grass (Cenchrus ciliaris L. aka Pennisetum ciliare L.). Genome-wide markers, generated using the DArTSeq platform and mapped onto the Setaria italica reference genome, were used for the genome-wide association study. The results revealed several markers associated with biomass yield and feed quality traits. A total of 78 marker–trait associations were identified with R2 values ranging from 0.138 to 0.236. The marker–trait associations were distributed across different chromosomes. Of these associations, the most marker–trait associations (23) were observed on Chr9, followed by Chr5 with 12. The fewest number of marker–trait associations were observed on Chr4 with 2. In terms of traits, 17 markers were associated with biomass yield, 24 with crude protein, 26 with TDN, 14 with ADF, 10 with NDF and 6 with DMI. A total of 20 of the identified markers were associated with at least two traits. The identified marker–trait associations provide a useful genomic resource for the future improvement and breeding of buffel grass.